2020
DOI: 10.1016/j.phrs.2020.104939
|View full text |Cite
|
Sign up to set email alerts
|

Review on the potential action mechanisms of Chinese medicines in treating Coronavirus Disease 2019 (COVID-19)

Abstract: The Coronavirus Disease 2019 (COVID-19) has been declared as a global pandemic, but specific medicines and vaccines are still being developed. In China, interventional therapies with traditional Chinese medicine for COVID-19 have achieved significant clinical efficacies, but the underlying pharmacological mechanisms are still unclear. This article reviewed the etiology of COVID-19 and clinical efficacy. Both network pharmacological study and literature search were used to demonstrate the possible action mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
221
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 19 publications
4
221
0
2
Order By: Relevance
“…Most of the related studies discuss the e cacy of TCM, while the studies about adverse reactions are few. During the treatment of COVID-19, the main adverse reactions include digestive symptoms, liver and kidney dysfunction, dyslipidemia and cardiotoxicity [23]. According to the available data, 14%~53% of COVID-19 patients have abnormal levels of ALT and AST.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the related studies discuss the e cacy of TCM, while the studies about adverse reactions are few. During the treatment of COVID-19, the main adverse reactions include digestive symptoms, liver and kidney dysfunction, dyslipidemia and cardiotoxicity [23]. According to the available data, 14%~53% of COVID-19 patients have abnormal levels of ALT and AST.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicines (TCM) are widely used in China and some Chinese communities outside China, with characteristics of low cost, good curative effect, short duration of treatment, and multiple targets. Numerous facts prove that it is feasible to treat human and animal diseases with TCM, which can effectively relieve symptoms, reduce the development from mild to moderate or severe, improve the cure rate, reduce mortality rate, and promote the recovery of patient by means of "multi-component, multi-target, multi-pathway" (Cantwell, 2010;Huang et al, 2020;Luo et al, 2020;Tong et al, 2020;Yuan et al, 2016).…”
Section: Traditional Chinese Medicinesmentioning
confidence: 99%
“…From the KEGG enrichment, the results indicates that the key signaling pathways of AE aganist COVID-19 were TNF, TLR, HIF-1 and NLRs signaling pathways that closely related to in ammation, immunity and oxidation process. Many studies of TCM against COVID-19 also reported that the anti-COVID-19 mechanism of TCM prescriptions including AE might involve the in ammation and immunity pathways liking TLR, JAK-STAT, TNF, AGE-RAGE, T cell receptor, IL-17 and so on 38,39 .…”
Section: Termmentioning
confidence: 99%